Effect of EDTA on TGF-β1 released from the dentin matrix and its influence on dental pulp stem cell migration - Lidiany Freitas GONÇALVES; Ana Paula FERNANDES; Leopoldo COSME-SILVA; Fabio Antonio COLOMBO; Natália Silva MARTINS; Thais Marchini OLIVEIRA; Tomaz Henrique ARAUJO; Vivien Thiemy SAKAI
Abstract: Bioactive molecules stored in dentin, such as transforming growth factor beta1 (TGF-b1), may be involved in the signaling events related to dental tissue repair. The authors conducted an in vitro evaluation of the amount of TGF-b1 released from dentin slices after treatment with 10% ethylenediaminetetraacetic acid (EDTA), 2.5% sodium hypochlorite (NaOCl) or phosphate-buffered saline (PBS), and the effect of this growth factor on stem cell migration from human exfoliated deciduous teeth (SHED). Sixty 1-mm-thick tooth slices were prepared with or without the predentin layer, and treated with either 10% EDTA for 1 minute, 2.5% NaOCl for 5 days or kept in PBS. Tooth slice conditioned media were prepared and used for TGF-b1 ELISA and migration assays. Culture medium with different concentrations of recombinant human TGF-b1 (0.5, 1.0, 5.0 or 10.0 ng/mL) was also tested by migration assay. The data were evaluated by ANOVA and Tukey's test. Optical density values corresponding to media conditioned by tooth slices either containing or not containing the predentin layer and treated with 10% EDTA were statistically greater than the other groups and close to 1 ng/mL. Increased rates of migration toward media conditioned by tooth slices containing the predentin layer and treated with PBS, 10% EDTA or 2.5% NaOCl were observed. Recombinant human TGF-b1 also stimulated migration of SHED, irrespective of the concentration used. EDTA may be considered an effective extractant of TGF-b1 from the dentin matrix. However, it does not impact SHED migration, suggesting that other components may account for the cell migration.